PKM Mengakses Internet Secara Cepat Bagi Siswa SD Inpres Panaikang I/1 Makassar - Zulhajji, Zulhajji; Mangesa, Riana T; Ruslan, Ruslan; Mudarris, Mudarris; Hamris, Hamidah (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
The main problem in implementing this Community Service activity is how to improve the quality of human resources for students of SD Inpres. Panaikang I/1 Makassar, South Sulawesi Province in utilizing information technology, especially accessing the internet quickly and accurately. The purpose and benefits of implementing the activity are to provide basic knowledge for students of SD Inpres. Panaikang I/1 Makassar, South Sulawesi Province to access the internet quickly and accurately. The basic idea behind this training activity is how students of SD Inpres. Panaikang I/1 Makassar, South Sulawesi Province no longer experience difficulties in seeking knowledge through the internet media. This training was also carried out using lecture, discussion, question and answer, and practice methods. From these results, it can be concluded that the ability to access the internet of students of SD Inpres. Panaikang I/1 Makassar, South Sulawesi Province has increased significantly. Keywords: Students SD Panaikang I/1 Competence, ICT